PENGARUH KOMPENSASI DAN DISIPLIN KERJA TERHADAP KINERJA PEGAWAI PADA DINAS SOSIAL KABUPATEN NAGAN RAYA - Zarman, Nasri; Karollah, Banta; Yudha, Ayi Satria (SI-MEN, 2022)
Performance is the result of a job that has a strong relationship with the organization's strategic goals, customer satisfaction and contributes to the economy. The purpose of this study was to determine the effect of compensation and work discipline on the performance of employees of the Social Service of Nagan Raya Regency. Location The research was conducted at the Social Service Office of Nagan Raya Regency, where there were 35 civil servants. The sampling method in this study used saturated sampling. In this study, the number of samples was 35 people, meaning that the entire population was used as a sample or saturated sample, while the analysis method used was multiple linear regression. The results showed that the compensation variable (X1) obtained a tcount of 2,340, for the work discipline variable (X2), the tcount was obtained. Amounted to 2,415. This shows that tcount > ttable is 2.03693, thus accepting Ha rejects Ho. While the Simultaneous F test of 5.728 with R2 of 56.90% employee performance is influenced by compensation (X1), and work discipline (X2). compensation and work discipline of employees at the Social Service of Nagan Raya Regency, the higher the employee's performance will be.